A study on the impact of financial crisis towards economic growth: East Asian perspectives / Nur Natasha Hassan - Hassan, Nur Natasha (2018)
Financial crisis is situations where the financial assets or institutions decreased in its nominal value. This situation not only affecting a nation but even worldwidely. There are many types of financial crisis such as, banking crisis, foreign and domestic debt crisis. In Malaysia, it faced the worst negative growth rate which at -7.35% in late 1998 due to Asian crisis breakout (Aini, Aziz, & Azmi, 2017). The outbreak has caused a lot of economy activity slowed down. The GDP growth decreased by 0.1% in the last quarter of 2008, and reached - l .51 in a particular situation in 2009. Economy growth of a country can be measured using Gross Domestic Product (GDP). Cerra and Saxena (2008) for example found out that the financial crisis is associated with largely declined in output. This research is to identify the variable that influence the growth of Gross Domestic Product. It is important to understand that Gross Domestic Product growth could bring significant impact to economy growth of a nation especially during financial crisis in selected East Asian countries which is at between year 1998-2015. The financial crisis expected to be happened repeatedly and predicted hence by this study we can understand the significant impact of the financial crisis and directly reduce its impacts towards economic growth of the country.